Boosting the thermoelectric performance of Bi2O2Se by isovalent doping. Issue 10 (3rd May 2018) - Tan, Xing; Lan, Jin‐Le; Hu, Kerong; Xu, Ben; Liu, Yaochun; Zhang, Peng; Cao, Xing‐Zhong; Zhu, Yingcai; Xu, Wei; Lin, Yuan‐Hua; Nan, Ce‐Wen
Abstract: N ‐type Bi2 O2 Se has a bright prospect for mid‐temperature thermoelectric applications on account of the intrinsically low thermal conductivity. However, the low carrier concentration of Bi2 O2 Se ( 10 15 cm −3 ) severely limits its thermoelectric performance. Herein, the boosting of the carrier concentration to 10 19 cm −3 can be realized in our La‐doped Bi2 O2 Se ceramic samples, which could be ascribed to the formation of isoelectronic traps and the narrowing of band gap, and contribute to a marked increase in the electrical conductivity (from 0.03 S cm −1 to 182 S cm −1 ). Our X‐ray absorption near‐edge structure spectra results reveal that a local disordering of oxygen atoms could be an important reason for the intrinsically low thermal conductivity of Bi2 O2 Se, and the point defects can also suppress the lattice thermal conductivity in La‐doped Bi2 O2 Se. The ZT value can be enhanced by a factor of 4.5 to 0.35 at 823 K for Bi1.98 La0.02 O2 Se as compared to the pristine Bi2 O2 Se. The coordinated optimization of electrical and thermal properties demonstrates an effective method for the rational design of high‐performance thermoelectric materials.